Castanea sativa Mill. Bark Extract Protects U‐373 MG Cells and Rat Brain Slices Against Ischemia and Reperfusion Injury. Issue 4 (28th November 2016) - Santulli, Chiara; Brizi, Claudia; Micucci, Matteo; Del Genio, Ambra; De Cristofaro, Assunta; Bracco, Federica; Pepe, Giuseppina Lucia; di Perna, Ilaria; Budriesi, Roberta; Chiarini, Alberto; Frosini, Maria
ABSTRACT: Ischemic brain injury is one of the most important causes of death worldwide. The use of one‐drug‐multi‐target agents based on natural compounds is a promising therapeutic option for cerebral ischemia due to their pleiotropic properties. This study assessed the neuroprotective properties of Castanea sativa Mill . bark extract (ENC) in human astrocytoma U‐373 MG cells subjected to oxygen‐glucose deprivation and reperfusion and rat cortical slices subjected to ischemia‐like conditions or treated with glutamate or hydrogen peroxide. Neuroprotective effects were determined by assessing cells or slices viability (MTT assay), ROS formation (DCFH‐DA assay), apoptosis (sub G0/G1 peak), nuclear fragmentation and chromatin condensation (DAPI staining) as well as changes in lysosomes and mitochondria morphology (Acridine Orange and Rhodamine123 staining, respectively). ENC treatment before injury on U‐373 MG cells (5–50 μg/ml) and cortical slices (50–100 μg/ml) provided neuroprotection, while lower or higher concentrations (100 μg/ml U‐373 MG cells, 200 μg/ml brain slices) were ineffective. ENC addition during reperfusion or after the injury was not found to be effective. The results suggest that ENC might hold potential as preventive neuroprotective agent, and indicate the importance of further studies exploring its mechanism of action. J. Cell. Biochem. 118: 839–850, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The aim of this study was to assess neuroprotection of Castanea sativa Mill. bark extract (ENC) in in vitro models of brain ischemia.